Capital Aset Pricing Model (CAPM) Revisited: The Context of Sharia-based Stocks with the Barakah Risk Premium Variable - Mahastanti, Linda Ariany; Asri, Marwan; Purwanto, Bernadus M.; Junarsin, Eddy (Jurnal Keuangan dan Perbankan, 2021)
The purpose of this study is to answer the question about the inconsistency of research results in the field of Islamic stock investment. This study uses literature for digging the uniqueness of Sharia stock investments which cannot be explained completely with a quantitative approach. In the last part of this research, we adjust the Capital Asset Pricing Model (CAPM) in the Sharia capital market based on a literature study. The classical finance theories such as CAPM need to adjust by incorporating the unique characteristics of faith-based investment products. The main difference between faith-based and conventional investment products lies in the presence of religious teachings that underlie the formation of these products. Consequently, investors employ not only the objective risk-and-return analysis to select investment choices, but also the subjective risk-and-return analysis based on Islamic teachings. Subjective gains (nonmonetary) are reflected by the barakah risk premium on which investors initially base their investment selection decisions between sharia-based and conventional stock investment. This research found a new variable called Barakah risk premium and Barakah return. This type of risk and return are very specific which is only found in sharia stock investments DOI : https://doi.org/10.26905/jkdp.v25i2.5572